Reading Comprehension for the Tenth Grade Students of SMAN 11 Jambi - Maghfira, Riska; Wennyta, Wennyta; Dewi, Kartika (Universitas Batanghari Jambi, 2023)
This research aimed to find out the effectiveness of using Listen – Read – Discuss (LRD) strategy towards students’ reading comprehension for tenth grade students at SMAN 11 Jambi. This method of research is quantitative and the design of this research is quasi-experimental design. This research used two classes, experimental class and control class, X-E7 as experimental class were taught by using Listen-Read-Discuss (LRD) Strategy, and X-E3 as control class were taught without Listen-Read-Discuss (LRD) strategy. Both classes consist of 36 students. This research used a test instrument with multiple choice questions with total number questions is 16 items. The test consisted of Narrative Text. The technique of data analysis is calculation the students’ score and analyzing using SPSS. The data was analyzed by T-test using SPSS for windows version 21.0. The result of this research is found that the mean score of post-test in experiment class with using LRD strategy was 87,86 and the mean of post-test in control class without using LRD Strategy was 77.67. Meanwhile, from T-test analysis found that the value of sig (2-tailed) was 0.000. As the result, it can be seen that 0.00 < 0.05 which mean that null hypothesis (Ho) was rejected ad the alternative hypothesis (Ha) was accepted. It means that there is significant effect of using Listen-Read-Discuss (LRD) strategy toward students reading comprehension at tenth grade students of SMAN 11 Jambi.